1993
DOI: 10.1021/tx00034a006
|View full text |Cite
|
Sign up to set email alerts
|

Expression in Escherichia coli of the flavin-containing monooxygenase D (form II) from adult human liver: Determination of a distinct tertiary amine substrate specificity

Abstract: The cDNA for a major component of the family of flavin-containing monooxygenases (FMOs) present in adult human liver (i.e., HLFMO-D) has been cloned and expressed in a prokaryotic system. Escherichia coli strain NM522 was transformed with pTrcHLFMO-D, and the HLFMO-D cDNA was expressed under the control of the Trc promoter. A variety of tertiary amine substrates [i.e., chlorpromazine and 10-[(N,N-dimethylamino)alkyl]- 2-(trifluoromethyl)phenothiazines] were efficiently oxygenated by HLFMO-D cDNA expressed in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…These differences could easily be related to several factors, including allelic variation, polymerase infidelity, and sequencing errors. In contrast, our sequence for human FMO3 differs markedly from the sequence of human FMO3 obtained from cDNA (14) 2 and a PCR product used for expression by Lomri et al (36). Alignment of these sequences shows 14 base substitutions and 17 positions where alignment requires introduction of a gap into one of the sequences (Table I).…”
Section: Resultsmentioning
confidence: 58%
“…These differences could easily be related to several factors, including allelic variation, polymerase infidelity, and sequencing errors. In contrast, our sequence for human FMO3 differs markedly from the sequence of human FMO3 obtained from cDNA (14) 2 and a PCR product used for expression by Lomri et al (36). Alignment of these sequences shows 14 base substitutions and 17 positions where alignment requires introduction of a gap into one of the sequences (Table I).…”
Section: Resultsmentioning
confidence: 58%
“…The quantitative assessment of FMO3 and FMO5 in human liver microsomal preparations (n = 5) demonstrates the utility of the recombinant enzymes for such studies. It has been shown previously that recombinant FMO3 exhibits the general properties of an FMO [12] and that qualitative comparisons between recombinant and microsomal human FMO3 can be made [45,46]. We have now been able to demonstrate conclusively that the catalytic properties of the enzyme in the two systems are virtually identical and that quantitative assessment of FMO isoforms in human hepatic microsomal samples can be made on the basis of studies with recombinant enzyme.…”
Section: Discussionmentioning
confidence: 62%
“…FMO3 has been cloned from human [13] and rabbit [16] and purified from rabbit [17], and FMO3 orthologs from macaque [14] and rat [18] have been identified. Results with purified and recombinant FMO3 [14,19,20] and with human samples [21,22] have provided evidence that the unique stereoselectivity of human liver microsomes for the metabolism of prochiral FMO substrates is a function of FMO3. However, FMO3 has not been quantitated in human samples nor has its specific activity (catalytic constant) been determined.…”
Section: Introductionmentioning
confidence: 99%
“…We interpret this as alternate substrate competitive inhibition of 5-DPT on chlorpromazine N-oxygenation. Previously, we showed that, compared with 5-DPT, chlorpromazine was an inferior substrate for FMO3, probably because of the shorter aliphatic side chain associated with this tertiary amine (Lomri et al, 1993). In contrast, 5-DPT possesses a more optimal aliphatic side chain length to place the tertiary amine further into the substrate-binding channel of FMO3 and afford more efficient N-oxygenation.…”
Section: Table 4 N-oxygenation Of Tertiary Amines By Human Fmo3mentioning
confidence: 94%
“…The N-oxygenation of chlorpromazine or 5-DPT was also determined as previously described (Lomri et al, 1993;Brunelle et al, 1997). In brief, a typical incubation mixture contained 50 mM potassium phosphate buffer (pH 8.4), 0.4 mM NADP ϩ , 0.4 mM glucose 6-phosphate, 1 IU of glucose-6-phosphate dehydrogenase, 0.8 mM DETAPAC, and 0 to 0.9 mg of MBP-FMO-His 6 .…”
Section: Methodsmentioning
confidence: 99%